Factor that influence customer's preference towards choosing theme park at Hello Kitty Town and Thomas Town Puteri Harbour/ Qistina Rosli - Rosli, Qistina (Faculty of Business Administration, 2018)
This chapter fundamentally focus on the background of this research. This chapter will summarize about the objectives of the study to see whether the objectives in the study are relevant or not. This chapter also will explain about the company profile, problem statement which is the main problem the company face and also purpose or this study.